The role of hygienic behavior in incidence of urinary tract infection among pregnant women referred to health center, Babol, 2002-04 - F Nasiri Amiri (Babol University of Medical Sciences, 2006)
BACKGROUND AND OBJECTIVE: The urinary tract infection (UTI) is a common problem in pregnant women. Since, UTI is caused by bacteria in the stool, hygienic behavior may affect the risk of contracting UTI. The purpose of this study was to determine the relationship between hygienic behavior and incidence of UTI in pregnant women.METHODS: This case-control study was performed on 250 pregnant women from 2002-2004. One hundred pregnant women from five health centers of Babol University of Medical Sciences for prenatal care, with a diagnosis of UTI by means of positive urine culture (as case group) were compared with one hundred fifty pregnant women (as control group). Both groups were matched according to age and social, economic, educational status and parity. Patients with recurrent UTI, chronic diseases like diabet and sickle cell anemia and consumption of immuno suppressive and antibiotic drugs were excluded from this study. Data was analyzed by SPSS. P<0.05 was considered significant.FINDINGS: Escherichia coli was the etiologic agent in 83% of cases. Odd ratio for any of the above variables were determined and risk factor for UTI were as follows: for sexual intercourse ≥3 times per week (OR=5.62), recent urinary tract infection (OR= 3.27), washing of genital pre coitus (OR= 2.16), washing of genital post coitus (OR= 3.89), voiding post coitus (OR= 8.62), washing of genital from back to front (OR= 2.69). Mean scoring hygienic behaviors in case and control group were 19.9±3.65 and 23.44±3.43, respectively.CONCLUSION: Hygienic habits and sexual behavior may play a significant role in the pregnant women with UTIs, with a positive bacterial urine culture, but evacuating of bladder after coitus was the most strongly associated variable.